AGE PATHOMORPHOSIS OF RECURRENT DEPRESSIVE DISORDERS - Скрипніков, А.М.; Герасименко, Л.О.; Гринь, К.В.; Gryn’ K. V. (World of Medicine and Biology, 2016)
Depression is one of the most common diseases worldwide. Research of recent years convincingly demonstrate a marked variability of depressive states. The aim of this work was to study age-related pathological changes in recurrent depressive disorder by study of some epidemiological indicators of morbidity recurent depression. clinical and epidemiological research method in the framework of analytical epidemiology, and the methods of mathematical analysis were applied. Statistically significant redistribution of patients recurent depression in more young persons with a corresponding but slight increase in the incidence in older age groups was revealed.